Analysis of "E-Patient UNS" Application System for Online Registration of UNS Hospital Patients - Haris Pujianto; Siti Rokhmah (International Journal of Computer and Information System (IJCIS), 2021)
The UNS Hospital E-Patient Application for Online Registration of UNS Hospital Patients is an application belonging to the UNS Hospital that can be used by old UNS Hospital patients to register for polyclinic visits online. Analysis of the "E-Patient Hospital UNS" application system from the results of an interview with the Head of the UNS Hospital Electronic Data Installation, which is the person in charge of the management of the application. The author also uses the results of the application user survey from January 1, 2020 s.d. November 27, 2020 to determine the level of customer satisfaction in conducting system analysis. The purpose of this system analysis is to find out how much the function or usefulness of this application system is to unravel or minimize the problems that become obstacles related to registration of polyclinic patient visits at UNS Hospital.